Manajemen Krisis Destinasi Wisata Pasca Bencana Tsunami Selat Sunda oleh Humas Pemerintah - Putri Widya Oktarini; Gayatri Atmadi (EDUTOURISM Journal Of Tourism Research, 2020)
The purpose of this research is to: (1). Obtained comprehensive descriptions of crisis management conducted in Tanjung Lesung tourist destination after Sunda Strait tsunami natural disaster by The Public Communication Bureau of the Ministry of Tourism. (2). Media options used by the Public Communications Bureau to support crisis management. This study uses an interpretive paradigm method with a qualitative descriptive approach and a case study as research strategy. The method of collecting data in this study was through direct interviews with the Ministry of Tourism's Public Communication Crisis Team. The results showed that the crisis management and strategy carried out was by conducting impact research and news in the media, making programming planning in the form of the appointment of aspokesperson, key public, publishing press releases regularly and organizing events. Besides that, the implementation involved several related communities in disseminating information.